1999
DOI: 10.1093/jat/23.6.535
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Abused Drugs and Antiabuse Chemotherapeutical Agents Stored at -20 C

Abstract: Stability is an important consideration in the use of specimens for accurate determination of analyte concentrations. To determine the long-term stability for analytes routinely analyzed by mass spectrometry in this laboratory, quality-control (QC) results were plotted versus time. The time required for the initial concentration to reach a specified level of deviation (i.e., 15%) was then determined from the slopes. QCs were prepared at 1-3 concentrations in drug-free matrix and stored at approximately -20 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 16 publications
5
24
0
1
Order By: Relevance
“…When samples were extracted, reconstituted, and stored in autosampler vials at Ϫ20°C, they were found to give accurate and precise results for up to 3 days of storage (Table 2). Previously, through reanalysis of clinical samples for buprenorphine, it was shown that statistically similar results were achieved for samples stored for 644 days at Ϫ20°C, but for samples stored 869 days under these conditions, the percentage of change in concentrations was significantly different (29). These direct results agreed well with those predicted from plots of concentrations in fortified sample versus time and extrapolation to a point where 15% deviation was found (i.e., 598 days).…”
Section: Stabilitysupporting
confidence: 68%
See 1 more Smart Citation
“…When samples were extracted, reconstituted, and stored in autosampler vials at Ϫ20°C, they were found to give accurate and precise results for up to 3 days of storage (Table 2). Previously, through reanalysis of clinical samples for buprenorphine, it was shown that statistically similar results were achieved for samples stored for 644 days at Ϫ20°C, but for samples stored 869 days under these conditions, the percentage of change in concentrations was significantly different (29). These direct results agreed well with those predicted from plots of concentrations in fortified sample versus time and extrapolation to a point where 15% deviation was found (i.e., 598 days).…”
Section: Stabilitysupporting
confidence: 68%
“…Short-and long-term stability studies on these analytes have been limited to buprenorphine (20,28,29). Current stability experiments focused on storage conditions that are relevant to the day-to-day analyses of these compounds.…”
Section: Stabilitymentioning
confidence: 99%
“…However, several studies have shown that change in concentrations of 11-nor-⌬ 9-THC-9-COOH after long-term storage was not extensive ( ! 15%) [29,30] . Second, we cannot rule out that women may wonder about specific aims for urine collection.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the possibility that metabolite concentrations were lower due to deterioration during storage (16). Urine specimens were stored frozen for an extended timeframe at −20°C before analysis in this study.…”
Section: Discussionmentioning
confidence: 99%